Direct and contextual effects of individual values on organizational citizenship behavior in teams - Arthaud-Day, Marne L.; Rode, Joseph C.; Turnley, William H. (My University, 2012)
We utilize Schwartz’s values theory as an integrative framework for testing the relationship between individual values and peer-reported organizational citizenship behavior (OCB) in teams, controlling for sex, satisfaction, and personality traits. Utilizing hierarchical linear modeling in a sample of 582 students distributed across 135 class project teams, we find positive, direct effects for achievement on citizenship behaviors directed toward individuals (OCB-I), for benevolence on citizenship behaviors directed toward the group (OCB-O), and for self-direction on both OCB-I and OCB-O. Applying relational demography techniques to test for contextual effects, we find that group mean power scores negatively moderate the relationship between individual power and OCB-I, while group mean self-direction scores positively moderate the relationship between self-direction and both OCB-I and OCB-O.
Keywords: Individual values; Organizational citizenship behavior; Schwartz's values theory; Achievement; Benevolence; Self-direction